Pengaruh Utang Luar Negeri, Ekspor, dan Impor Terhadap Pertumbuhan Ekonomi Indonesia Periode 1996-2013 - Saputra, I Gede; Kesumajaya, I Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
ABSTRACT The Indonesia government get the additional capital resources from foreign debt. Every year the foreign debt has increased, different with the progress of export and import values are unstable. On the other side of Indonesia economic growth has fluctuated. The research objective is to determine the effect of Indonesia's foreign debt, exports, and imports simultaneously or partially to Indonesia's economic growth period 1996-2013. The data in this study is the development of Indonesia's economic growth, foreign debt, export, and import the period 1996-2013. Data were analyzed using multiple linear regression. The results showed Indonesia's foreign debt, exports, and imports simultaneously significant effect on the economic growth of Indonesia period 1996-2013. With the amount of R2 is 0.875, this means that 87.5 percent of Indonesia's foreign debt variables, exports and imports affect Indonesia's economic growth. For partial test consists of foreign debt is negative and significant, imports are negative but not significant, and exports are positive and significant to economic growth of Indonesia period 1996-2013.
Keywords: Keywords: Economic Growth, Foreign Debt, Export, Import